An SMS based system for surveillance of wheat rust diseases: a pilot initiative in Central Anatolia region in Turkey1. (27th July 2015) - Dusunceli, F.; Stocchi, A.; Scaduto, C.; Mancini, F.; Birisik, N.; Sahin, M.; Selcuk, S.; Muminjanov, H.; Asikoglu, T.; Mert, Z.; Akan, K.; Cetin, L.; et al.
Abstract : Rust diseases ( Puccinia spp.), namely stripe, leaf and stem rusts, are among the major diseases of wheat. Their management requires integrated approaches including timely surveillance, speedy communication and rapid response. This surveillance system was developed in order to facilitate participation of extension offices (in provinces/districts) in the survey of wheat rust diseases and sharing of information quickly. The SMS based system was tested as a pilot tool in the Central Anatolia region of Turkey connecting 25 districts in 5 provinces through an SMS network during the rust development period (April–July) in 2013. The observations from 268 fields indicated that leaf rust and stem rust development was insignificant in the districts covered, occurring in only 2.3% and 1.9% of the fields respectively. Stripe rust prevalence was higher occurring in 44.8% of the fields. Of the inspected fields 2.5% had infected plant incidences between 15% and 40% requiring control measures. Using the SMS reports received from the extension officers, the system facilitated daily monitoring of rust development and exchange of observations among the relevant institutions, also sending out alert messages to designated authorities as necessary. The study demonstrated that the system can serve as a rapid surveillance and communication tool to facilitate timely decision making and rapid response to prevent wheat rust epidemics.